'Do you seek to be a specialist therapeutic residential care provider for children and young people who have complex needs?' Some thoughts on the necessary criteria for practice in specialist residential services - Richard Cross (Scottish Journal of Residential Child Care)
This paper explores aspects of the provision of specialist therapeutic residential child care for children between the ages of 6 and 18 years who have experienced significant loss and neglect in their lives. The views expressed are purely those of the author and do not refer to any particular service. These views are meant to provoke some thought around how we define specialist therapeutic residential services.